Tajhin Sorah Dan Tajhin Sappar: Eksplorasi Makna Simbolis Dalam Bingkai Budaya Madura - Puspitasari, Desi; Saksono, Suryo Tri (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2024)
This study aims to uncover the symbolic meanings of two traditional Madurese dishes, Tajhin Sorah and Tajhin Sappar, through a semiotic approach. These dishes not only serve as food but also as cultural representations that reflect the values and traditions of the Madurese people. A qualitative descriptive method was employed to analyze the components of these culinary items, including ingredients, presentation, and associated social practices. The findings reveal that Tajhin Sorah, associated with the Islamic New Year celebration, symbolizes unity and good fortune, while also strengthening social bonds through sharing practices. Meanwhile, Tajhin Sappar, served during the month of Safar, represents a unique blend of local ingredients that reflect the life philosophy of the Madurese community. In conclusion, these dishes are not merely food but also vital symbols in preserving cultural identity and social relationships. The study suggests that a deeper understanding of traditional culinary practices is essential for cultural preservation efforts.